Соціальна справедливість як один із основних принципів надання соціальних послуг - Шумна, Л. П.; Шумная, Л. П.; Shumnaja, L. (My University, 2012)
The system measures necessary for putting into practice the principle of social justice, social services, must include: assessment of income and material conditions of the recipient of services; identify the reasons due to which the person fell into the diffi cult life circumstances; the selection of individual social security services; evaluate the effectiveness of aid on the basis of the feedback system.
Шумна Л. П. Соціальна справедливість як один із основних принципів надання соціальних послуг / Л. П. Шумна / Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 37-42.
Keywords: надання соціальних послуг в Україні; соціальна справедливість; право соціального забезпечення в Україні; предоставление социальных услуг в Украине; социальная справедливость; право социального обеспечения в Украине; provision of social services in Ukraine; social justice; social security law in Ukraine